Ampliação da consciência por meio da calatonia e da arteterapia - Arcuri, Irene Pereira Gaeta (2009)
The main purpose of this research is understand the experience of expansion of consciousness, lived along de process of psychotherapy after Calatonia and expressed by means of making mandalas and its subsequent associations. It deals with a qualitative research, based in clinical cases interpreted through the lumen of Jungian Analytic Psychology. The expansion occurred always that some unconscious content was integrated to the consciousness in this process. When the unconscious content was retained by mechanisms of defense, pressuring and provoking the increase of the unconscious energetic level, the emergency of a new symbol, enabled by Calatonia and expressed in the mandalas and/or in the process of associations, allowed the transformation of the structure of the consciousness and the assimilation of the unconscious content, that formerly couldn t be assimilated. Both experiences, corporal and artistic, in the process of Calatonia and the accomplishment of mandalas, based on the singularity of the relationship between patient and therapist, reproduced similar conditions of the first relations between people, propitiating the transformation of the complexes and the expansion of consciousness